Territórios da infância em Ondjaki: uma estética da pós-colonialidade angolana - Coutinho, Fernanda Maria Abreu (2014)
Considering childhood as an epistemological category that evokes many questions about the social representations in contemporary times, this work discusses the work of the Angolan poet and prose writer Ondjaki (Ndalu de Almeida) through the perspective of the child’s voice that predominates in several of his texts. Based on Agamben (2005) and Spivak (2010), we try to verify how this infant voice perceives and represents the Angolan context of postcoloniality in both fictional and nonfictional texts by Luanda. For this reason, we have selected Ondjaki’s works which were published in the first decade of the 21st century, namely the moment when the author was firmed as an intellectual and fiction writer.